Using the Green Infrastructure as an Economic Sustainable Tool for Improving Urban Life in Emerging Countries Urban Poverty Areas Greater Cairo Case Study - Ahmed Elewa, Ahmed Khaled (European Journal of Sustainable Development, 2014)
Through the last decades rapid urbanization in the emerging countries was producing bad urban quality. This urbanization of poverty is responsible of the phenomenon of the current spreading of slums in those countries main cities, Yet the common urban solutions for improving the urban life in those areas always require a high-cost budget which usually surpassing the financial ability of the local governments. The study main objective is to evaluate the possibility of using the Green Infrastructure as an economic sustainable tool for improving the urban life in urban poverty areas of emerging countries. An analytical study was done based on the case of Greater Cairo city informal areas as urban poverty areas. The study has clarified how the elements of the Green Infrastructure could be used as an effective economic and sustainable tool through its environmental, urban, and social roles, for the improvement of urban poverty areas in the emerging countries main cities, Also has shown that the Green Infrastructure depends on available local natural elements, local experts experience and the most important. Its affordable cost, which make it an effective economic tool. Key Words: Green Infrastructure, Economic Sustainability, Emerging Countries